Representations of Sexual Violence in Islamic Boarding Schools on Nu. or.id and Mubadalah.id:: A Corpus-Assisted Critical Discourse Analysis - Maharani, Elektra Aulia; Darmayanti, Nani; Citraresmana, Elvi (Universitas Jambi, Magister Program of English Education Department, 2026)
Islamic boarding schools (pesantren) across two Indonesian online news outlets: NU Online and Mubadalah.id. Employing a mixed-methods approach, the study integrates Fairclough's three-dimensional Critical Discourse Analysis (CDA) framework, transitivity analysis within Halliday and Matthiessen's Systemic Functional Linguistics (SFL), and corpus-assisted discourse analysis using the SketchEngine platform. The data corpus comprises 25 articles from NU Online and 18 articles from Mubadalah.id published between 2022 and 2025, all addressing cases of sexual violence within pesantren environments. The findings reveal that, despite both outlets being rooted in the organisational tradition of the Islamic mass organisation Nahdlatul Ulama, they construct markedly divergent discursive representations of sexual violence. NU Online constructs its discourse through the predominance of verbal processes attributed to institutional sources, thereby positioning sexual violence as the object of authoritative statements and producing narratives that tend to foreground institutional positioning and boundary maintenance. Mubadalah.id, by contrast, employs relational and existential processes to frame sexual violence as a structural phenomenon embedded in power relations and gender inequality, while affording comparatively greater representational space to survivors' voices. These discursive divergences are inseparable from the distinct institutional positions, editorial orientations, and value systems articulated by each outlet. This study affirms that media reporting is never ideologically neutral, and that grammatical choices in news texts carry direct implications for the social construction of victims, perpetrators, and religious institutions.